106k views
5 votes
Solve the equation by factoring. z2 − 6z − 27 = 0

a.z = –3 or z = 9


b.z = –3 or z = –9


c.z = 3 or z = 9


d.z = 3 or z = –9

User Bpiec
by
5.3k points

1 Answer

3 votes

Answer:

The answer is x= 9 and -3


You must fine 2 number that multiply to equal -27 and add to equal -6


(x-9) (x+3)

Then equal the parts of the binomial to zero


x - 9 = 0

x + 3 = 0


You must get x by its self.

When you do so, you'll have the answer as -3 and 9


Explanation:


User Basalex
by
5.0k points